2008
DOI: 10.1016/j.jtcvs.2008.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of single-dose and 24-hour multiple-dose antibiotic prophylaxis for cardiac surgery

Abstract: Single-dose cefazolin used as antibiotic prophylaxis in cardiac surgery is associated with a higher surgical site infection rate than the 24-hour, multiple-dose cefazolin regimen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
31
0
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 29 publications
2
31
0
5
Order By: Relevance
“…That significant difference was due to the significantly higher single dose SSWI rate (5%) than with multiple doses (1.7%) (p = 0.007). Notably, DSWI and endocarditis rates were comparable for both groups (respectively 1.9% and 1.2% for single dose vs. 1.2% and 0.2% with 24-h regimen) comparable to those of current study [9].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…That significant difference was due to the significantly higher single dose SSWI rate (5%) than with multiple doses (1.7%) (p = 0.007). Notably, DSWI and endocarditis rates were comparable for both groups (respectively 1.9% and 1.2% for single dose vs. 1.2% and 0.2% with 24-h regimen) comparable to those of current study [9].…”
Section: Discussionsupporting
confidence: 79%
“…A recent systematic review and meta-analysis showed that perioperative antibiotic prophylaxis lasting ≥24 hours might be more effective than shorter regimen but the findings were limited by the heterogeneity of antibiotic regimens and the risk of bias in the published studies [1]. Some studies compared single-dose vs longer antibiotic prophylaxis [1], but very few used the same antibiotic in both arms [8,9] and only the former compared singledose vs 24-hour doses of the same antibiotic. Tamayo and associates, in their monocentric unblinded prospective study, compared 2 cefazolin doses over 42 months: the single-dose was associated with significantly higher SSI rate (8.3%) than with multiple-doses (3.6%) (p = 0.004).…”
Section: Discussionmentioning
confidence: 99%
“…Of the patients admitted to intensive care units (ICUs), the incidence of severe sepsis or septic shock is between 9% and 37% [1][2][3][4]. In spite of recent advances in treatment with antibiotics and critical care therapy, sepsis still results in a high mortality rate; it is typically between 40% and 60% in the case of septic shock [1][2][3][4][5]. Septic shock and multiple organ dysfunction syndrome (MODS) are the most common causes of death in ICUs [4].…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, inhospital patients are also at risk for multiple postoperative events (eg, myocardial infarction [MI], congestive heart failure, acute renal failure, strokes) [1][2][3][4]16,18,19]. These comorbidities complicate the evaluation of the impact of VAP on mortality [17].…”
Section: Introductionmentioning
confidence: 99%